Investigation Giant Placental Chorioangioma Associated with Neonatal Sepsis-like Disease: A Case Report - Adauto Barbosa; Nei Menezes; Gesmar Volga Haddad; Vania Silami Lopes (Iranian Journal of Neonatology, 2015)
Giant chorioangioma is a placental tumor associated with gestational complications such as preeclampsia, polyhydramnios and hemorrhage. In addition, this tumor might lead to the incidence of non-immune fetal hydrops, heart failure, anemia, thrombocytopenia, weight loss and death among neonates. In this case report, the clinical image of a term newborn (weighing 2800 g) with one-minute Apgar score of 7 was suggestive of sepsis on the second day of birth. Moreover, epistaxis, petechia, anemia, thrombocytopenia, hypothermia, cardiomegaly and hepatosplenomegaly were detected in the neonate, which required blood transfusion and antibiotic therapy. However, in case of chorioangioma in the gestational history, it was possible to detect the motive for a clinical sepsis-like disease. According to the pathophysiological explanation, this tumor functions as a "dead space", increasing the rate of blood ejection with subsequent fetal heart failure, anemia through intratumoral hemorrhage or fetal-maternal transfusion, and consumption or intratumoral sequestration resulting in disseminated intravascular coagulation. After blood transfusion, all treatment procedures, including antibiotic therapy, were suspended due to the recovery of the newborn.